Implementasi Metode FKNN (Fuzzy K-Nearest Neighbor) Untuk Diagnosis Penyakit Tanaman Kentang - Jiwandani Andromeda; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Solanum taberosum (Potatoes) is one of the staple foods of humans because it is one of the tubers that has a good content. The content of protein and carbohirat can be fairly balanced so it is good for health. Potato production in Indonesia experienced a 9.82% reduction in production, from 1,176,304 tons in 2009 and in 2010 to 1,060,805 tons. Potato production in 2009 also decreased by 16.51 tons / hectare to 15.95 tons / hectare. Potato cultivation so far has several obstacles such as diseases and pests. Late blight is a major disease in potato plants. This disease has a lot of genetic heterogeneity so that plants become vulnerable to broken. Losses caused are fairly high in potato plants, especially in weather with high humidity. One of the solutions to make this plant easy to develop is by using varieties that have genetic resistance to the P. infestans race found in wild potato species. However, the genetic utilization of wild potato plants cannot be used for the development of commercial potato plants because they have different genetic makeup. To reduce failures in potato cultivation, software technology is currently needed to help detect diseases early on potatoes in order to facilitate farmers in potato cultivation.